Systematic review of fertility‐related psychological distress in cancer patients: Informing on an improved model of care. Issue 1 (20th November 2018) - Logan, Shanna; Perz, Janette; Ussher, Jane M.; Peate, Michelle; Anazodo, Antoinette
Abstract: Objective: Cancer patients experience reproductive concerns from diagnosis through to survivorship. However, research has yet to investigate the degree of fertility‐related psychological distress at different treatment time points: diagnosis, treatment, and survivorship. Currently, cancer patients are offered fertility counselling at the time of diagnosis, to assist fertility preservation decision making. A systematic review of the short‐term and long‐term psychological impact of infertility in cancer patients would inform on an improved, longitudinal model of psychological care. Methods: A systematic review of the literature was conducted in January 2018 utilising electronic databases Medline, EMBASE, PSYCH Info, Web of Science, and SCOPUS. An initial search identified 708 potentially relevant studies. Literature was assessed that reported on fertility‐related psychological distress experienced by male and female cancer patients of reproductive age (<45 years) across oncology treatment time points. Results: A total of 47 papers were included within the final review. Fertility‐related psychological distress persists from diagnosis through to survivorship, with cancer patients reporting a range of negative emotional experiences brought about by threatened infertility. In survivorship, reproductive concerns, unfulfilled desire for a child, nulliparous status, and early menopause were linked to higher rates of mental health disorders and psychological distress. Conclusions: Fertility‐related psychological distress is prevalent and persistent in cancer patients and survivors. As such, patients and survivors would greatly benefit from fertility‐related psychological support implemented into standard practice from diagnosis through to survivorship. A revised model of care is proposed.